Knowledge and self-care behavior among heart failure patients in South India - Prima Jenevive Jyothi D'Souza; Linu Sara George; Ganesh Paramasivam; Tom Devasia; Anice George; Baby S. Nayak; P Kusumavathi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Heart failure (HF) is a chronic condition with significant public health concerns. HF necessitates adequate knowledge and adherence to self-care for enhanced quality of life and decreased rehospitalization. This study aimed to explore knowledge and self-care behavior in patients with HF. MATERIAL AND METHODS: The study was conducted in cardiology wards of a tertiary care hospital and the design was a randomized controlled trial. The baseline data (before the intervention) from 160 HF patients enrolled in a randomized controlled trial were analyzed. Knowledge and self-care behavior were measured using the Dutch HF Knowledge Questionnaire (score ranging from 0 to 15) and European HF Self-care Behavior Scale-9 (score ranging from 0 to 100). Higher scores indicated better self-care behavior and knowledge. Descriptive statistics such as frequency, percentage, mean, and standard deviation and inferential statistics such as independent sample t-test and ANOVA were performed. RESULTS: The majority (75.0%) were men with a mean age of 56.1 ± 7.9 years. A significant proportion had hypertension (65%), diabetes (58.7%), or both comorbidities (40.6%). Most exhibited a left ventricular ejection fraction <30% (60.6%) and New York Heart Association class II (43.1%). The mean knowledge and self-care behavior scores were 7.1 ± 2.0 and 45.0 ± 12.4, respectively. Over half of the participants had inadequate self-care behavior (51.2%), and 88.3% lacked sufficient knowledge about HF. Medication adherence was high (87.0%) among the participants, while only 3.1% reported regular weight monitoring and 32.3% exercised regularly. CONCLUSIONS: There was a lack of HF-related knowledge and inadequate self-care behavior for HF management. Effective interventions to improve disease-related knowledge may lead to better self-care behavior and improve clinical outcomes.